Efficient Nash equilibrium based cloud resource allocation by using a continuous double auction - Dawei Sun; Guiran Chang; Chuan Wang; Yu Xiong; Xingwei Wang (2010 International Conference On Computer Design and Applications, 2010)
To allocate cloud resources efficiently and obtain the maximum economic benefit are the major goals of the cloud resource providers and users. The objective of this paper is to present a novel cloud resource allocation algorithm named NECDA to overcome some of the shortcomings of the current mechanisms. A cloud resource allocation model of m*n type based on M/M/1 queuing system is established first. Then the Nash equilibrium mode is applied in the cloud computing among m*n allocation environment, the optimization objective of each allocation is performance-QoS and economic-QoS, and the Nash equilibrium is achieved by taking advantage of the continuous double auction in each step, each provider agent determines its requested value based on its workload, and each user agent determines its bid value based on the remaining time and resources. By simulations, we conclude that the NECDA is more suited to cloud computing environments and can better meet the QoS requirements of users.